Phenol hydrodeoxygenation and descriptor based on TM@Mo2C single-atom catalysts - Jiehang Wei; Shouqin Mu; Wenjuan Wang; Yuxin Xu; Mengjia Fu; Yingtao Liu; Xin Wang (Fuel, 2027)

Isolation and food-relevant evaluation of a novel lytic Kayfunavirus phage vB-EcoP-B10 for controlling STEC on food-contact surfaces and in raw beef - Yuxin Mu; Min Li; Xiangqi Bai; Qianhong Li; Xiaodong Xia; Ting Zhou; Chunling Zhang; Ying Yu; Yanna Dai; Jifeng Pu; Hu Pan; Xin Wang (Food Research International, 2026)

Critical overview of Peracetic acid-based advanced oxidation processes: Evolution, fundamentals and water treatment applications - Yongbo Yu; Jiaxin Yu; Haochen Zhang; Yongchao Mu; Yanjun Xin; Bin Zhang; Jun Ma (Chemical Engineering Journal, 2026)

Salinity dynamics in a dryland large lake over the past 2 kyr and its driving forces - Muhammad Farqan; Lixiong Xiang; Wenjia Wang; Jiayu Deng; Xiaoyan Mu; Xin Liu; Ruiqi Min; Chong Huang; Mingjie Sun; Luciane Fontana; Xiaozhong Huang (Quaternary Science Reviews, 2026)

Integrating optical remote sensing and airborne gamma for lithological classification using an artificial neural network: A case study in Wuliji, North China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Enhancing composite emulsion stability through electrostatic modulation of polysaccharides-whey protein isolate interactions for probiotic encapsulation - Wei-Gang Xin; Yu-Hang Jiang; Yu-Han Dong; Yu-Hang Hou; Mu-Ying Du; Amel Ahmed Ibrahim; Zsolt Zalán; Hua-Yi Suo (Food Chemistry, 2026)

Sulfuric acid-induced microphase separation strengthens poly(acrylic acid) hydrogels - Zheng Luo; Yuan Feng; Meng Mu; Xing Zhang; Heng Liu; Mingmin Zhang; Xin Su; Yujun Feng (Chemical Engineering Journal, 2026)

Bioinspired heterogeneous wettability patterned oil-absorbing felt for efficient remediation of complex oily wastewater and oil spills - Bohao Qi; Chaoying Zhang; Xin Hu; Huan Liu; Yuanyuan Ren; Yang Li; Yiming Li; Yingchun Mu; Mutai Bao (Chemical Engineering Journal, 2026)

Halolitoreus marinus gen. Nov., sp. nov. and Halolitoreus rarus sp. nov., halophilic archaea isolated from diverse coastal tidal flats, and proposal of the novel family Halolitoreaceae fam. Nov. in the order Halobacteriales within the class Halobacteria - Jing Hou; Guo-Liang Xu; Shun Tan; Ya-Ling Mao; Yu-Jie Xin; Mu Cheng; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Nitrogen fertilization drives bacterial turnover versus fungal persistence for straw-derived C and N stabilization in a wheat-maize rotation - Guocui Ren; Xiuli Xin; Haowei Ni; Xianfeng Zhang; Lan Mu; Wenliang Yang; Shuchun Ge; Shaopu Pang; Anning Zhu (Soil and Tillage Research, 2026)

Combined exposure to flumethrin and hexaconazole induces synergistic oxidative, metabolic, and immune dysregulation in honeybees - Tao Cang; Ying Wang; Xinfang Li; Xin Peng; Qihe Zhao; Xiyan Mu; Guojun Zhou; Yanhua Wang (Journal of Hazardous Materials, 2026)

Endogenous copper manipulation based on multifunctional gold nanoparticles elicit precise and self-reinforcing photothermal-chemodynamic therapy for effective treatment of metastatic breast cancer - Haoyu Wang; Xiaolin Yu; Handan Zhang; Jie Liu; Ruozhen Ma; Li Chen; Tao Liu; Xinran Shi; Wenyun Mu; Xin Chen (Chemical Engineering Journal, 2026)

Aging-Related Changes in the Injury Response of the Peripheral Nervous System - Yue-Yan Cen; Mu-Yun Wang; Qin-Xuan Song; Xin-Lin Gao; Cheng Zhou; Chun-Jie Li; Fei Liu; Yan-Yan Zhang; Jie-Fei Shen (Neuroscience Bulletin, 2026)
Peripheral nerve injury (PNI) significantly impairs patients’ quality of life, with elderly individuals experiencing particularly severe consequences due to aging-related declines in neuronal injury response and repair capabilities. Processes of the generation and transmission of injury signals, axonal disruption, initiation of regeneration, and the elongation of regenerating axons, as well as the subsequent reinnervation by these axons, are all significantly influenced by aging. These alterations are closely associated with changes in mitochondrial function, neuronal transport systems, a persistent inflammatory milieu, and various microenvironmental non-neuronal cells. Therefore, this review synthesized the pivotal role of aging in the multifaceted regulation of the nervous system following PNI and highlighted promising molecular regulatory mechanisms in the signaling pathways. Furthermore, it identified critical areas for future research, including unresolved questions in age-associated injury responses, potential targets for pharmacological intervention, and emerging therapeutic strategies meriting consideration for research and development.

Two decades of methane budgets at the sub-national scale in China - Pengfei Zhao; Zhen Zhang; Guanghui Huang; Zhenxuan Wang; Josep G. Canadell; Philippe Ciais; Huilin Chen; Shengqian Chen; Jason Blake Cohen; Fan Dai; Peng Gong; Robert B. Jackson; et al. (Science Bulletin, 2026)

A multi-source precipitation blending method combining hydrological model-guided precipitation adjustment and double transfer learning-based data merging - Jingyang Wang; Xiang Li; Ruiyan Wu; Xiangpeng Mu; Jiahua Wei; Yuefei Huang; Shenglong Gu; Dongqin Yin; Xin Tao; Keyan Xu (Journal of Hydrology, 2026)

Sulfur vacancy-rich MoS2 nanoflowers as electron shuttles boost Fe(VI) activation for efficient micropollutant degradation - Lian Wu; Xin Zhou; Zi-Yi Han; Hui-Zhi Mu; Lu Wang; Yu-Lei Liu; Jun Ma (Journal of Hazardous Materials, 2026)

A composite conductive hydrogel loaded with alginate/gelatin microspheres with micro-environmentally induced smart temporal regulation for acute myocardial infarction treatment - Lei Mu; Tongyang Li; Bowen Qiao; Ruonan Dong; Congcong Zhang; Xin He; Peixue Ling; Zheng Wang; Baolin Guo (Carbohydrate Polymers, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Optimisation and bioactivity evaluation of Brassica rapa L. seed oil extraction using novel green dimethyl ether extraction - Wan Xiao-Fu; Yimuranjiang Subuhati; He Tian; Miao-Miao Wang; Jia-Xin Yang; Le Pan; Mu-Chun Li (Natural Product Research, 2026)

Differentiated mechanisms of microplastic accumulation and migration in lakes, wetlands and reservoirs: A comparative study of three ecosystem types in the North China Plain - Guangyin Sun; Siyu Hao; Xin Meng; Xinyu Cao; Yongchao Mu (Journal of Environmental Chemical Engineering, 2026)

Hybrid energy system based on co-firing municipal sludge coupled with power generation: energy balance, carbon emissions, and thermo-economic analysis - Zhaolei Meng; Zongguo Wen; Xin Meng; Fan Fei; Yanfei Mu; Gang Li; Tao Zhou; Quanjie Li; Yiqun Meng (Journal of Cleaner Production, 2026)

Integration of network toxicology, transcriptomics and metabolomics reveals the novel neurotoxic mechanisms of diazepam and its metabolites - Xu Xiaodong; Li Jiaxin; Li Zimeng; Yang Zhen; Qiao Lu; Xu Jinhua; Qi Bohao; Hu Xin; Ren Yuanyuan; Li Jiongtang; Mu Yingchun (Food and Chemical Toxicology, 2026)

Comprehensive Assessment of Potentially Toxic Elements in Riparian Zone Soils of Kuitun River Basin: Distribution, Ecological Risks and Human Health Implications - Yaru Wang; Chang Zhou; Xin Liu; Yilin Fan; Hongchao Mu; Jiankang Wang; Junfeng Li; Pu Wang (Water, Air, & Soil Pollution, 2026)

A potent human neutralizing antibody targeting the receptor-binding site in the glycoprotein gp350 of Epstein-Barr virus - Qingtai Liang; Qian-Ying Zhu; Xin-Yan Fang; Jing Wei; Yi-En Xu; Yanan Zuo; Guo-Long Bu; Chu Xie; Sisi Shan; Cong Sun; Zheng Liu; Linqi Zhang; et al. (Science China Life Sciences, 2026)

Integrating Biotic and Abiotic Measures Enhances Early Ecosystem Functionality in Degraded Grasslands - Yang Lei; Chang-Ning Li; Tuo Yao; Yakov Kuzyakov; Chen Zhang; Shan-Mu He; Jia-Li Chai; Jie Bai; Yi-Xin Zhang; Shuang-Xiong Li (Journal of Soil Science and Plant Nutrition, 2026)

Corrigendum to ‘ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection’ [Pesticide Biochemistry and Physiology 220 (2026) 107056] - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

Real-time analysis of drillstring dynamic insertion and system vibration-induced wellbore wear in offshore directional well - Feng Tang; Yongsheng Liu; Lin Chai; Zongyang Mu; Xin Lei; Qiang Sun (Ocean Engineering, 2026)

A Full-Mission integrated navigation framework for Shallow-Sea AUV based on GPR-Assisted EKF - Yang Shen; Xin Zhang; Mengnan Hao; Xiaokai Mu (Ocean Engineering, 2026)

Gestational dibutyl phthalate exposure impairs the ovarian reserve in offspring mice through METTL14-m6A-mediated PI3K-AKT-FOXO3a activation - Yan Zhang; Fuqing Yi; Ying He; Yidan Ma; Xinyi Mu; Yanqing Geng; Xin Yin; Rufei Gao; Liping Yan; Xuemei Chen; Junlin He (Journal of Hazardous Materials, 2026)

Non-photosynthetic microorganisms drive the transformation of bioinert emerging contaminants through photoinduced singlet oxygen production - Qi Huang; Jie Huang; Xin Zhang; Mu-Cen Yao; Yan-Yun Hu; Yi Hu; Zheng-Shuang Hua; Guo-Ping Sheng (Journal of Hazardous Materials, 2026)

Atomically precise Pd4 cluster on monolayer MoS2 for efficient overall water splitting - Yuxin Xu; Jing Ma; Tao Ma; Jiehang Wei; Mengjia Fu; Wenjuan Wang; Shouqin Mu; Xin Wang; Yingtao Liu (Fuel, 2026)

Enhancement of the gas/water interfacial properties of heat-induced α-lactalbumin via inhibiting the thermal aggregation: impacts of gypenoside concentrations - Shumin Guo; Zhishen Mu; Xin Wen; Hongyu Li; Zhanmei Jiang; Yun Chen (Food Hydrocolloids, 2026)

Saccharomyces cerevisiae BR14 fermentation modulates volatile flavor profile of milk and enhances its protective efficacy against DSS-induced colitis in mice - Zhiyong Mu; Yijin Yang; Yongjun Xia; Xin Song; Lianzhong Ai (Food Bioscience, 2026)

Tailoring nitric oxide-release hydrogel incorporating MSC-derived exosomes for multimodal therapy of diabetic foot ulcers - Kaijie Zhao; Xuan Tian; Qijian Wei; Yuteng Li; Mingzhuo Zhou; Anhui Mu; Xin Yan; Shilei Ni; Pei Liu (Chemical Engineering Journal, 2026)

Study on the mechanism of mixed biochar enhancing methane production in anaerobic digestion of corn straw - Huilin Zhang; Siyu Zhang; Pujie Wei; Xinyue Zhao; Hong Chang; Zeyan Mu; Xu Zhang; Wei Liu; Xudan Liu; Xiaohong Su; Xin Wang (Biocatalysis and Agricultural Biotechnology, 2026)

Bioaccumulation and Elimination, and Risk Assessment of Diazepam in Carp (Cyprinus Carpio) - Zhen Yang; Xiaodong Xu; Ying Li; Xin Hu; Jinhua Xu; Lu Qiao; Huiwu Sun; Yingchun Mu (Bulletin of Environmental Contamination and Toxicology, 2026)

Targeting ACSL4: A potential strategy to alleviate deoxynivalenol-mediated intestinal ferroptosis, oxidative stress, and immunosuppression in Channa argus - Yi-Ran Zhao; Tong-Hao Wang; Ze-Xin Zhao; Xiao-Tian Niu; Hong-Ming Lv; Yan-Bing Li; Yang Cao; Mu-Yang Li (Aquaculture, 2026)

Distribution and evolution of distress in embankment-bridge transition sections of the Gonghe–Yushu Expressway in degrading permafrost regions - Bingyan Li; Minghao Liu; Yanhu Mu; Jing Luo; Xin Ju; Fei Yin; Fan Yu; Yunhui Huang (Transportation Geotechnics, 2026)

Identification of a novel and thermostable laccase from Bacillus velezensis GLY4 and its application in the biotransformation of aflatoxins - Xin Zhang; Binbin Ouyang; Wei Xu; Hongbin Sun; Wanmeng Mu (Food Bioscience, 2026)

Corrigendum to “Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus” [Fish Shellfish Immunol. 165 (2025) 110566] - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2026)

Amorphous phosphate-mediated Schottky junction at Mo2N-based heterojunction interface to accelerate interfacial electron transfer for boosted photocatalytic hydrogen evolution - Yu-pei Li; Zi-xin Qi; Xiao-jing Wang; Jun Zhao; Jun Yang; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2026)

Climatological characterisation and trends of extreme winds and their application to power transmission lines in China - Hongyu Wang; Cong Jiang; Feifei Mu; Kai Liu; Rui Mao; Xin Yin (Natural Hazards, 2026)

COLREGs-compliant ship collision avoidance strategy based on proximal policy optimization algorithm - Qiaosheng Zhao; Tianyu Yang; Chaoxu Mu; Qiyu Chen; Tao Luo; Mingkai Liu; Xin Wang (Frontiers in Marine Science, 2026)
The safe and efficient collision avoidance of multiple ships is essential for maritime navigation and intelligent shipping systems. In this paper, we propose a novel COLREGs-compliant multi-ship collision avoidance strategy based on deep reinforcement learning. A cooperative training framework using the Proximal Policy Optimization (PPO) algorithm enables multiple ship agents to learn optimal collision avoidance actions while considering the interactions and motions of neighboring ships. Encounter situation awareness mechanisms and carefully designed reward functions are integrated to ensure strict adherence to the International Regulations for Preventing Collisions at Sea (COLREGs), while a multi-objective optimization approach embedded in the reward function balances collision risk, navigational efficiency, route smoothness, and destination achievement. Extensive simulations covering diverse ship encounter scenarios demonstrate the effectiveness, robustness, and COLREGs compliance of the proposed strategy, highlighting its practical potential for multi-ship navigation systems.

Seasonal dynamics of microbial diversity and ecological functions in the river estuary area of Loushan River - Xin Hu; Chengci Liu; Jinhua Xu; Zhiyang Zhao; Hongyu Jin; Xiaodong Xu; Lu Qiao; Zhen Yang; Jincheng Li; Mutai Bao; Lei Huang; Yingchun Mu (Journal of Hydrology, 2026)

Highly efficient Xe/Kr separation within a metal-organic framework featuring continuous molecule traps - Yan-Long Zhao; Xiang-Yu Li; Xuefeng Bai; Mu-Zi Li; Xin Zhang (Chemical Engineering Journal, 2026)

Ground validation of dust multi-properties analyzer onboard Tianwen-2 - Xu Tan; Cunhui Li; Jiajie Wang; Zhongcheng Mu; Zecheng Cui; Meng Chen; Xin Ren; Xiaodong Liu; Yan Su; Wei Wang; Renhao Tian; Jiawei Li (Advances in Space Research, 2026)

Physics-informed neural network for hydraulic prediction in open-channel water transfer projects with sparse monitoring data - Zhongbin Li; Tong Mu; Xin Li; Pengcheng Li; Jiangang Feng; Hui Xu; Chunsheng Liu; Shangtuo Qian (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Ecological implications of biodegradable and conventional microplastics: Dissolved organic matter bioavailability and microbial response in marine systems - Yu-xin Wu; Hao-yu Wang; Wang-chao Chu; Yuan-yuan Gao; Mu-qiu Xia; Fei-fei Liu (Journal of Hazardous Materials, 2025)

Ni/Al-based additives for deep desulfurization of high-sulfur coal: Cooperative desulfurization and sulfur migration behavior - Zheng-Zhi Zhang; Zhan-Ku Li; Jing-Tao Yao; Mu-Xin Liu; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Cai Wang; Zhi-Ping Lei; Shi-Biao Ren; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2025)

Iron-doped biocarriers enhanced nitrogen removal from saline wastewater in an unplanted constructed wetland-microbial electrolytic cell system - Longqiang Yi; Changyuan Liu; Xinyu Rong; Kexin Li; Ruina Zhang; Xin Su; Xinting Mu; Li Wan; Yinghai Wu; Rui Han (Journal of Environmental Management, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

CRLS1 influences liver metastasis in colon cancer by regulating lipid metabolism pathways - Junbo Mu; Donghao Li; Honglei Shen; Mengyuan Cao; Luye Zhang; Cangxue Wang; Keni Sun; Han Wang; Yiyang He; Kejun Liu; Xin Huang; Quankun Liang; et al. (Functional & Integrative Genomics, 2025)

Transcriptome analysis reveals no obvious unintended effects in the spleen of CRISPR/Cas9-mediated CD163 and pAPN double-knockout pigs - Zhi-Guo Liu; Nan Wang; Wan-Jie Wang; Lei Huang; Shun-Shun Chi; Yu-Xin Nie; Mao-Sha Yuan; Ya-Ru Sun; Yu-Lian Mu; Kui Li (Functional & Integrative Genomics, 2025)

BmeIF4E2 promotes AcMNPV infection in the silkworm, Bombyx mori, by direct interaction - Xin-Yi Ding; Jiang-Zhi Su; Wen-Jing Yu; Qian-Qian Jiao; Zuo-Min Shao; Ai-Jun Wan; Sheng Qin; Xia Sun; Xue-Yang Wang; Ding-Ding Lü; Mu-Wang Li (Pesticide Biochemistry and Physiology, 2025)

Enhancing granular sludge stability: Insights from the superior performance of biofilms - Xin Wang; Xiaoran Feng; Zhibang Mu; Mingshan Wang; Chengjian Yang; Guohui Lv; Zhihua Li (Journal of Water Process Engineering, 2025)

Distribution, ozone formation potential, and health risk assessments of VOCs in automotive seat cushion leather during finishing process - Zhaohui Yang; Chuanhui Mu; Xin Cheng; Yuling Tang; Jianfei Zhou; Bi Shi (Journal of Hazardous Materials, 2025)

Rapid formation of acetaldehyde and its influence on ozone formation in a petrochemical industrialized region - Can Cui; Yujiao Zhu; Xiaoyu Yan; Xin Zhang; Min Zhao; Jiangshan Mu; Xuelian Zhong; Jinghao Tang; Yanqiu Nie; Cong An; Wanghui Chu; Yue Sun; et al. (Journal of Environmental Sciences, 2025)

Emissions and carbon isotopic signatures of polycyclic aromatic compounds (PAHs, OPAHs) produced by coking in China - Jiajie Li; Ling Mu; Xiaofan Li; Xiaofeng Liu; Huiling Bai; Chuanyang Feng; Xin Jiang; Ying Wei; Chenhui Li (Environmental Pollution, 2025)

Isopropanol gas sensor based on CoSnO3/SnO2/Zn2SnO4 ternary heterostructure with high response - Fangling Zhou; Zhuangzhuang Mu; Gaoliang Chen; Zhenyu Yuan; Renze Zhang; Xin Yan; Fanli Meng (Chemical Engineering Journal, 2025)

Synergistic Co single-atom/nanoparticle catalysis enables stable hydrogenation of levulinic acid to gamma-valerolactone with formic acid - He Huang; Wei Zhang; Jianrong Zeng; Mengke Liu; Han Lin; Liwen Mu; Xin Feng; Xiaohua Lu; Lilong Zhang; Jiahua Zhu (Chemical Engineering Journal, 2025)

Optimizing biogas residue composting: Impact of biochar and zeolite co-loaded with lignocellulose-degrading microbial agents on degradation, humification, and microbial ecology - Hong Chang; Ruian Lin; Xiaohong Su; Xinrui Xu; Wei Liu; Yilin Zhang; Zeyan Mu; Xin Wang; Anina James; Junting Pan (Journal of Environmental Chemical Engineering, 2025)

Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2025)

Phase-interfacial engineering of 2H@1 T-WS2-x cocatalyst to accelerate H2 production on SnS2 - Jianchun Wang; Nan Mu; Ruixin Xu; Xin Hong; Yanyu Liu; Wei Zhou (Chemical Engineering Journal, 2025)

Spatiotemporal dynamics of retrogressive thaw slumps on the Qinghai-Tibet Plateau: integrating UAV-LiDAR and GPR - Fan Yu; Jing Luo; Fujun Niu; Zhanju Lin; Bingyan Li; Yanhu Mu; Xin Ju; Minghao Liu; Guoan Yin; Zeyong Gao; Xiaolong Zhao; Chengming Zhang (Landslides, 2025)

Trend changes in tourism climate suitability in China and the impact of multiple atmospheric circulation patterns - Zikang Ren; Huarong Zhao; Xinzhi Mu; Kangming Shi; Xin Jin (International Journal of Biometeorology, 2025)

Design and testing of the clam vibration harvester's V-shaped double-spiral harvesting roller brush based on DEM-MBD - Li Hangqi; Mu Gang; Li Xiuchen; Wu Hao; Xu Bin; Liu Fawei; Sun Zhenyin; Zhang Qian; Zhang Hanbing; Xin Mingjin; Zhang Guochen (Aquacultural Engineering, 2025)

Enantiomeric meroterpenoids from Rhododendron capitatum and their anti-inflammatory activity - Hang Xie; Qing Shi; Yu-Meng Miao; Xin-Yu Sun; Jin-Chang Huang; Chun Lei; Qing Mu; Jing-Ya Li; Ai-Jun Hou (Phytochemistry, 2025)

A runoff prediction approach based on machine learning, ensemble forecasting and error correction: A case study of source area of Yellow River - Jingyang Wang; Xiang Li; Ruiyan Wu; Xiangpeng Mu; Baiyinbaoligao; Jiahua Wei; Jie Gao; Dongqin Yin; Xin Tao; Keyan Xu (Journal of Hydrology, 2025)

Decabromodiphenyl ethane induces intrauterine growth restriction by suppressing placental angiogenesis via TWIST2/NAT10-mediated ac4C-dependent TGF-β1 mRNA stabilization - Run Ling; Xin Yin; Liyao Ma; Yan Zhang; Yidan Ma; Rufei Gao; Yanqing Geng; Xinyi Mu; Xuemei Chen; Fangfang Li; Junlin He (Journal of Hazardous Materials, 2025)

Exploring Allium mongolicum Regel flavonoids alleviation of deoxynivalenol-induced gut inflammation and flesh-quality improvement based on muscle-intestinal axis in a Channa argus model - Zhe Yu; Zhuang Xiong; Yi Wang; Zhi-Qiang Gao; Ke-Xin Lu; Ying Zhang; Mu-Yang Li; Yuan-Xi Yue (Food Bioscience, 2025)

Nature-Inspired cell membrane-coated artificial biocatalysts with Os-single-atom sites and multienzyme-Mimetic activities for targeted tumor therapy - Jiawei Wang; Jing Wu; Zijun Ma; Xin Xie; Lu Zhao; Xiao Luo; Wenjun Liu; Bo Ren; Qi Li; Ling Li; Shengdong Mu (Chemical Engineering Journal, 2025)

Interlayer covalent bridging covalent organic polymers for highly efficient photocatalytic organic synthesis - Xia Zhao; Ai-Cen Li; Dan Yang; Yong-Hui Wang; Xin Mu; Cong Wang; Hua-Qiao Tan (Chemical Engineering Journal, 2025)

Synergistic microstructure regulation of coal tar pitch based‑carbon by pre-oxidation and iodine treatment for its high-plateau-capacity sodium storage - Yuli Wei; Qing Wang; Qing Liu; Rongzhe Wang; Shaohua Luo; Lixiong Qian; Yahui Zhang; Pengqing Hou; Shengxue Yan; Xin Liu; Jing Guo; Wenning Mu (Chemical Engineering Journal, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

CAFM: a freeware for geochemical data processing and concentration–area fractal modeling and its application for identifying uranium anomalies of different genesis - Jun-Ting Qiu; Jiang-Kun Li; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Applied Geochemistry, 2025)

Study on freeze-thaw damage and mechanical properties of fractured rock mass grouting reinforcement in alpine region open-pit mines - Xin Wang; Wenqiang Mu; Lianchong Li; Tianhong Yang; Miaomiao Bai; Shigui Du (International Journal of Rock Mechanics and Mining Sciences, 2025)

Screening of enzymes for bi-functional whey protein hydrolysates: virtual enzymolysis, fragmentomics, and molecular docking in silico - Ruoyun Gao; Fanhua Kong; Guangqing Mu; Xin Zhao; Jianbo Cheng; Fang Qian (Food Research International, 2025)

Shear Failure Mechanism of Fiber-Reinforced Concrete–Rock Interface Under Freeze–Thaw Conditions - Xin Wang; Wenqiang Mu; Lianchong Li; Tianhong Yang; Shigui Du; Miaomiao Bai (Rock Mechanics and Rock Engineering, 2025)

Exploring Morphological Indicators for Ramet Age Discrimination of Fargesia nitida Based on Growth Patterns - Xiu-xin Mu; Kai-ming Lei; Hong-ou Sun; Pei-gang Kuang; Yue Zhang; Guo-lan Wang; Tao Zeng (Journal of Plant Growth Regulation, 2025)

Synergistic recovery for Al and Ga within high-alumina fly ash by carbochlorination using the response surface method - Wang Long; Zhao Xin-xin; Zhang Zi-mu; Zhang Ting-An; Lv Guo-Zhi; Dou Zhi-He; Liu Yan; Fan zhi-yu (Waste Management, 2025)

Exploring heterogeneity in evacuation decision of urban residents between utility and regret decision rules under a flood hazard - Zeqian Jin; Yichen Wang; Chen Li; Chengcheng Yu; Xin Ye; Jiantao Mu (Sustainable Cities and Society, 2025)

Formyl-phloroglucinol meroterpenoids with Nrf2 inhibitory activity from Eucalyptus globulus leaves - Wei Liu; Yaodong Xia; Lejie Zhang; Xin Chen; Zhuo Zhang; Yu Mu; Jialin Xu; Xueshi Huang; Liya Li (Phytochemistry, 2025)

In vivo imaging tool: High-brightness NIR-II “J-aggregates” based on TICT suppression strategy - Taihe Han; Shuai Mu; Qin Huang; Jiaxing Sun; Xin Lv; Yanxia Zhang; Xiaoyan Liu; Wei Guo; Haixia Zhang (Chemical Engineering Journal, 2025)

Triple microenvironment synergy engineering by grain boundaries of hydrophilic Cu electrode for boosting low-concentration nitrate electroreduction - Xin Wang; Qinian Wang; Mu Yuan; Xu Cheng; Bo Zhang; Ke Zhang; Lili Wang; Chao Wu; Xing Zhang (Chemical Engineering Journal, 2025)

Dicyclohexyl phthalate derails trophoblast function and lipid metabolism through NDRG1 by targeting PPARα:RXRα - Yu Zhang; Yanqing Geng; Yan Zhang; Yidan Ma; Xin Yin; Zhuxiu Chen; Xinyi Mu; Rufei Gao; Xuemei Chen; Fangfang Li; Junlin He (Toxicology, 2025)

Immune restoration mechanism analysis of Akkermansia PROBIO in mice treated with cyclophosphamide through Re-balancing microbiota composition - Junpeng Zhang; Xin Ma; Wenjiao Du; Guangqing Mu; Xiaomeng Wu (Food Bioscience, 2025)

Activation of NR2A-Wnt-TLR2 Signaling Axis in Satellite Glial Cells of the Dorsal Root Ganglion Contributes to Neuropathic Pain Induced by Nerve Injury in Diabetic Mice - Yan-Yan Zhang; De-Xin Zhu; Mu-Yun Wang; Ya-Ting Yi; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen (Molecular Neurobiology, 2025)

Evolution Mechanism of Water-Conducting Channels and Disaster Triggering Induced by Fault Zone Failure in a Mining Roadway - Jian Chen; Lianchong Li; Wenqiang Mu; Xin Wang; Bo Ren (Mine Water and the Environment, 2025)

Hydrothermal drivers of seasonal and interannual dynamics of soil respiration and its temperature sensitivity in a temperate semiarid shrubland - Shengjie Gao; Xin Jia; Xiaoyan Jiang; Yanmei Mu; Charles P.-A. Bourque; Peng Liu; Shugao Qin; Yun Tian; Wenjing Chen; Tianshan Zha (Agricultural and Forest Meteorology, 2025)

Unrecognized role of photosynthetic bacteria in aquaculture water purification: Producing singlet oxygen to degrade residual pharmaceuticals - Mu-Cen Yao; Qi Huang; Hong-Xuan Xie; Xin Zhang; Guo-Ping Sheng (Water Research, 2025)

Anaerobic co-digestion of antibiotic fermentation residues and corn stalks for biogas production and elimination of antibiotic resistance genes - Beibei Yan; Xin Chen; Zhi Wang; Jian Li; Tangwei Li; Lan Mu; Guanyi Chen (Fuel, 2025)

Nanocomposite hydrogel with multiple metal ions coupling for effective treatment of bacteria infected wound via cascade catalysis and tissue regeneration - Yating Liu; Wenyun Mu; Yu Wang; Tao Liu; Zhenzhen Peng; Xin Chen (Chemical Engineering Journal, 2025)

Oxidative Stress-mediated Loss of Hippocampal Parvalbumin Interneurons Contributes to Memory Precision Decline After Acute Sleep Deprivation - Yu-zhu Gao; Kai Liu; Xin-miao Wu; Cui-na Shi; Qiu-li He; Hai-peng Wu; Jian-jun Yang; Hao Yao; Mu-huo Ji (Molecular Neurobiology, 2025)

Development and evaluation of high-throughput HD-Marker arrays in pacific white shrimp (Litopenaeus vannamei) - Mingyang Liu; Zhihui Yang; Xin Huang; Qifan Zeng; Qianqian Mu; Zhenyuan Xu; Zijian Li; Pingping Liu; Shi Wang; Jingjie Hu; Zhenmin Bao (Aquaculture, 2025)

Parkinson's Disease and the Microbiota-Gut-Brain Axis: Metabolites, Mechanisms, and Innovative Therapeutic Strategies Targeting the Gut Microbiota - Zhao Ran; Ben-Rong Mu; Dong-Mei Wang; Xin-Huang; Quan-Hong Ma; Mei-Hong Lu (Molecular Neurobiology, 2025)

Effect of cold plasma synergistic acid induction on the quality characteristics of casein gel - Yu Zhang; Hongchi Zhou; Xin Wang; Guangqing Mu; Fang Qian (Food Chemistry, 2025)

Intelligent veins recognition method for slope rock mass geological images in complex background noise - Niu Wen-jing; Chen Yuan-xin; He Ben-guo; Chen Guang-mu; Qiu Zhen-hua; Fan Wen-yu (Computers & Geosciences, 2025)

Molecular level simulation and analysis of removal of sulfur, nitrogen and carbon residue in residual oil hydrotreating process - Xinglong Qin; Ye Ji; Guangqing Cai; Tiansheng Wang; Yu Du; Guangyu Mu; Jian Zhang; Xuezhi Duan; Xin Pu; Xin Han; Lei Ye; Jichang Liu (Chemical Engineering Journal, 2025)

Lignin enhanced shape memory polyimide with superior mechanical property and performance - Qiang Wang; Xin Li; Mengxin Kan; Hui Gao; Shanshan Liu; Xingxiang Ji; Handong Mu; Zhuangzhuang Mao; Zhanhui Yuan (Chemical Engineering Journal, 2025)

Geosites Associated with Paleovolcanic Landscapes and Paleontology in Hoboksar Mongol Autonomous County, Xinjiang Uygur Autonomous Region, NW China - Hong-Xu Mu; Qing-Wei Song; Jun-Ting Qiu; Long-Xin Xu; Xin-Min Rui (Geoheritage, 2025)

Combination mechanism and dimethyl ether removal performance of organic-bound water in kitchen waste - Jipeng Sun; Wei Zhu; Jun Zhong; Biao Mu; Xin Wang; Xinyi Wang; Yucheng Xu; Jun Cao; Naixi Lin (Waste Management, 2025)

Immobilization and transformation behavior of V(IV) and V(V) by ferrihydrite and lepidocrocite - Jia-li Li; Chun-dan Gan; Xin-yue Du; Yan-li Ren; Mu-cheng Xu; Jin-yan Yang (Process Safety and Environmental Protection, 2025)

Effects of luxS gene on biofilm formation and fermentation property in Lactobacillus plantarum R - Yang Chen; Xin Fan; Xiaoqing Zhu; Junfeng Xiao; Yang Mu; Wenyue Wang; Chao Wang; Mingye Peng; Mengzhou Zhou (Food Research International, 2025)

Efficient image inpainting of microresistivity logs: A DDPM-based pseudo-labeling approach with FPEM-GAN - Zhaoyan Zhong; Liguo Niu; Xintao Mu; Xin Wang (Computers & Geosciences, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Diatom assemblages indicated ecological shifts over the past two centuries in Bosten Lake, northwest China: Natural and anthropogenic forcings - Muhammad Farqan; Lixiong Xiang; Lan Jiang; Wenjia Wang; Min Zheng; Xiaoyan Mu; Xin Liu; Xueqing Song; Zezhou Zhu; Ramamoorthy Ayyamperumal; Xiaozhong Huang (Quaternary International, 2025)

Lignite degraded by Trichoderma citrinoviride: Products, processes and mechanisms - Xingyu Mu; Meitong Li; Jianhua Tian; Wenjiao Yuan; Hui Shen; Ruijie Zhang; Shuwei Li; Xin Feng; Xuening Fei; Yuhong Xie (International Biodeterioration & Biodegradation, 2025)

Single-atom nanozyme immunoassay with electron-rich property for clinical patient cancer detection - Qingshan Liu; Guo Li; Yang Cao; Yaoyao Ren; Qiong Qin; Lei Li; Hao Zhang; Qi Xin; Xiaoqun Gong; Lingyu Zhao; Shu Zhang; Yonghui Li; et al. (Chemical Engineering Journal, 2025)

Improved PM2.5 prediction with spatio-temporal feature extraction and chemical components: The RCG-attention model - Ao Li; Yafei Wang; Qianqian Qi; Yunfeng Li; Haixia Jia; Xin Zhou; Haixin Guo; Shuyang Xie; Junfeng Liu; Yujing Mu (Science of The Total Environment, 2024)

Cooperative control of leader–follower ships with prescribed performance - Xinjiang Wei; Chengmei Mu; Huifeng Zhang; Xin Hu (Ocean Engineering, 2024)

The relationships between flavor substances and microbial communities during the fermentation of Chinese traditional red sour soup - Xin Zhang; Zhenyu Wang; Xianbing Xu; Xin Mu; Baifeng Fu; Jinxiu Xu; Shuhong Ye; Ming Du (Food Bioscience, 2024)

Characterization of whey protein isolate aggregation induced by different acidic substances: Triggered by disulfide bond formation and recombination - Xin Wen; Zhishen Mu; Munkh-Amgalan Gantumur; Akhunzada Bilawal; Zhanmei Jiang; Ligang Zhang (Food Hydrocolloids, 2024)

Efficient phosphate recovery and treatment of high-phosphorus wastewater using sodium alginate-immobilized microspheres based on aluminum-rich water treatment plant sludge - Guorui Li; Wei Zhu; Jun Zhong; Jipeng Sun; Yichao Wang; Biao Mu; Xin Wang; Yucheng Xu (Environmental Pollution, 2024)

Modelling the frost cracking behavior in clayey soils: A peridynamic approach - Junwei Zheng; Jian Wang; Yang Lu; Xin Gu; Manuel Pastor; Saeid Moussavi Tayyebi; Yanhu Mu; Tian Wang (Computers and Geotechnics, 2024)

Microbial transformation of lignite into methane: Insights from anaerobic-activated sludge systems - Ruijie Zhang; Meitong Li; Wenjiao Yuan; Xin Feng; Xuening Fei; Xingcheng Zhao; Gangzhen Jiao; Hui Shen; Xingyu Mu; Yuhong Xie (Bioresource Technology Reports, 2024)

Durability and Permeability Characteristics of Consolidated Bodies After Grouting in Freeze–Thaw Rock in Cold Regions - Xin Wang; Wenqiang Mu; Lianchong Li; Tianhong Yang; Jiang An; Jian Lu (Rock Mechanics and Rock Engineering, 2024)

A deep learning-based global tropical cyclogenesis prediction model and its interpretability analysis - Bin Mu; Xin Wang; Shijin Yuan; Yuxuan Chen; Guansong Wang; Bo Qin; Guanbo Zhou (Science China Earth Sciences, 2024)

Enhancement and Preservation of Tufa Geosites in the Baishuitai Region, Yunnan Province, Southwest China - Hong-Xu Mu; Qing-Wei Song; Gui-Hua Wu; Long-Xin Xu (Geoheritage, 2024)

Correction: Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

Oncogenic miRNAs dependent photothermal-immunotherapy enhanced by on-demand manipulation of immunosuppressive microenvironment using engineered gold nanoparticles for effective treatment of primary and metastatic tumor - Li Chen; Yu Hu; Wenyun Mu; Tao Liu; Wenjun Tang; Lin Weng; Yanmin Zhang; Xin Chen (Chemical Engineering Journal, 2024)

S2CPL: A novel method of the harvest evaluation and subsoil 3D cutting-Point location for selective harvesting of green asparagus - Si Mu; Nianzu Dai; Jin Yuan; Xuemei Liu; Zhenbo Xin; Xiangbao Meng (Computers and Electronics in Agriculture, 2024)

Generation and emission mechanism of polycyclic aromatic hydrocarbon (PAHs) during the coking process in Shanxi, China - Ziye Liu; Ling Mu; Chuanyang Feng; Xiaofan Li; Tian Liu; Xin Jiang; Huiling Bai; Xiaofeng Liu (Science of The Total Environment, 2024)

Risk assessment of high maturity lacustrine shale oil reservoir based on pore-fracture connectivity and decane accessibility, Ordos Basin (China) - Jianjiang Wen; Mengdi Sun; Bingsong Yu; Mehdi Ostadhassan; Tomasz P. Blach; Yeping Ji; Phung Vu; Liliana de Campo; Chunming Wu; Jingfu Mu; Zijie Ren; Xin Tian; et al. (Marine and Petroleum Geology, 2024)

Effects of straw management and N levels on gross nitrogen transformations in fluvo-aquic soil of the North China Plain - Guocui Ren; Xianfeng Zhang; Jinbo Zhang; Lan Mu; Xiuli Xin; Yiming Yun; Anning Zhu; Shuchun Ge (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Near-infrared and multifunctional fluorescent probe enabled by cyanopyridine cyanine dye for bisulfite recognition and biological imaging - Shangcong Gu; Yan Huang; Xinxin Li; Haotian Xin; Haoran Mu; Yan Zhang; Keyi Li; Guiyi Yang; Songfang Zhao; Duxia Cao (Journal of Hazardous Materials, 2024)

Effects of neonicotinoid residues on non-target soil animals: A case study of meta-analysis - Yuxuan Cao; Wenting Zhao; Jinrui Zhang; Daniel M. Figueiredo; Mingyu Zhao; Siyang Ren; Hongyu Mu; Yiyi Li; Huan Lu; Haoyuan Shi; Xin Li; Jindong Li; et al. (Journal of Hazardous Materials, 2024)

Tin isotope heterogeneity and baseline of the upper continental crust - Jia-Xin She; Weiqiang Li; Edith Kubik; Frédéric Moynier; Xiang-Long Luo; Jun Mu; Shichao An; Chang-Zhi Wu; Zhongya Hu; Junfeng Ji (Geochimica et Cosmochimica Acta, 2024)

Inclusion of Lonicerae flos improved anaerobic fermentation and antioxidant activity of mixed silage (agro-residue and alfalfa) - Lin Mu; Xin Cao; Yating Wang; Qinglan Wang; Zhifei Zhang (Animal Feed Science and Technology, 2024)

Vegetation factors and atmospheric dryness regulate the dynamics of ecosystem water use efficiency in a temperate semiarid shrubland - Yanmei Mu; Xin Jia; Ziqi Ye; Xulin Guo; Shaorong Hao; Tianshan Zha; Yuqing Zhang; Cong Han; Shengjie Gao; Fei Xing; Shugao Qin; Peng Liu; et al. (Journal of Hydrology, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

Preparation, taste characterization, and evaluation of oyster composite products with increased umami and salty - Baifeng Fu; Shuzhen Cheng; Xin Zhang; Junjie Yi; Zhishen Mu; Ming Du (Food Bioscience, 2024)

Exploring Cr(VI)-induced blood-brain barrier injury and neurotoxicity in zebrafish and snakehead fish, and inhibiting toxic effects of astaxanthin - Mu-Yang Li; Yan-Chao Shi; Wan-Xin Xu; Lei Zhao; Ai-Zhong Zhang (Environmental Pollution, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Integrated decision support framework for construction land reduction projects prioritization in China: a multi-criteria decision analysis approach - Lei He; Yuming Zhu; Jiahe Zhou; Xin Zheng; Bingxu Mu; Qiang Li (Environment, Development and Sustainability, 2024)

Marinobacter sediminicola sp. nov. and Marinobacter xiaoshiensis sp. nov., Isolated from Coastal Sediment - Jing An; Run-Yuan Mao; Shu-Xin Wang; Jing Zhang; Zong-Jun Du; Da-Shuai Mu (Current Microbiology, 2024)

Halobacterium yunchengense sp. nov., Natronomonas amylolytica sp. nov., Halorientalis halophila sp. nov., Halobellus salinisoli sp. nov., halophilic archaea isolated from a saline lake and inland saline soil - Ling Cui; Yao Hu; Xin-Xin Li; Xue Ma; Mu Cheng; Shun Tan; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Retraction Note: Evaluating an economic application of renewable generated hydrogen: A way forward for green economic performance and policy measures - Baijun Wu; Bingfeng Zhai; Huaizi Mu; Xin Peng; Chao Wang; Ataul Karim Patwary (Environmental Science and Pollution Research, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

An Experimental Study on Fracturing Response and Slurry Flow of High-Pressure Grouting in Fractured Rock - Wenqiang Mu; Lianchong Li; Honglei Liu; Bo Ren; Jian Chen; Xin Wang (Rock Mechanics and Rock Engineering, 2024)

Halomarina litorea sp. nov., Halomarina pelagica sp. nov., Halomarina halobia sp. nov., and Halomarina ordinaria sp. nov., Halophilic Archaea Isolated from Coastal and Inland Saline Soil - Mu Cheng; Xin-Xin Li; Jing Hou; Heng-Lin Cui (Current Microbiology, 2024)

Biocatalytic Au10 clusters for sepsis management via modulation of systemic inflammation - Qi Xin; Sufei Zhou; Lijie Zhang; Si Sun; Di Liu; Hao Wang; Xiaoyu Mu; Xiaoxing Fang; Qi Chen; Huanhuan Qiao; Xiao-Dong Zhang; Ruiping Zhang (Chemical Engineering Journal, 2024)

Insights into atmospheric trace gases, aerosols, and transport processes at a high-altitude station (2623 m a.s.l.) in Northeast Asia - Ye Shan; Yujiao Zhu; Yanbi Qi; Yu Yang; Jiangshan Mu; Mingxuan Liu; Hongyong Li; Ji Zhang; Yanqiu Nie; Yuhong Liu; Min Zhao; Xin Zhang; et al. (Atmospheric Environment, 2024)

Multi-omics insights into biogeochemical responses to organic matter addition in an acidic pit lake: Implications for bioremediation - Zhixiang She; Jin Wang; Xin Pan; Ding Ma; Yijun Gao; Shaoping Wang; Xin Chuai; Yang Mu; Zhengbo Yue (Water Research, 2024)

Maternal exposure to beta-Cypermethrin disrupts placental development by dysfunction of trophoblast cells from oxidative stress - Xiaoli Tang; Yanqing Geng; Rufei Gao; Zhuxiu Chen; Xinyi Mu; Yan Zhang; Xin Yin; Yidan Ma; Xuemei Chen; Fangfang Li; Junlin He (Toxicology, 2024)

Late gestational exposure to fenvalerate impacts ovarian reserve in neonatal mice via YTHDF2-mediated P-body assembly - Fei He; Xinyi Mu; Yan Zhang; Yongheng Wang; Jianwei Geng; Yanqing Geng; Yidan Ma; Xin Yin; Rufei Gao; Xuemei Chen; Junlin He (Science of The Total Environment, 2024)

Maternal exposure to ZIF-8 derails placental function by inducing trophoblast pyroptosis through neutrophils activation in mice - Yu Jiang; Yanqing Geng; Rufei Gao; Zhuxiu Chen; Jun Chen; Xinyi Mu; Yan Zhang; Xin Yin; Xuemei Chen; Fangfang Li; Junlin He (Food and Chemical Toxicology, 2024)

Characteristics and sources of peroxyacetyl nitrate (PAN) in the rural North China Plain: Results from 1-year continuous observations - Xin Liu; Xiaowei He; Chenglong Zhang; Yifei Song; Shuyang Xie; Chengtang Liu; Pengfei Liu; Yuanyuan Zhang; Yujing Mu; Junfeng Liu (Journal of Environmental Sciences, 2024)

Jurassic integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Jianguo Li; Xin Rao; Lin Mu; Xiaohui Cui; Xin Li; Hui Luo; Peixue Liu (Science China Earth Sciences, 2024)

Genome-based taxonomy of genera Haloarcula and Halomicroarcula, and description of six novel species of Haloarcula - Xue Ma; Yao Hu; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Dry-season length affects the annual ecosystem carbon balance of a temperate semi-arid shrubland - Yanmei Mu; Xin Jia; Ziqi Ye; Tianshan Zha; Xulin Guo; T. Andrew Black; Yuqing Zhang; Shaorong Hao; Cong Han; Shengjie Gao; Shugao Qin; Peng Liu; et al. (Science of The Total Environment, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Dynamic responses of multi-story structural systems with separated gravity and lateral resisting systems under seismic action considering connection semi-rigidity effects - He Zhao; Xin-Yu Qian; Xiao-Gang Liu; Hong-Bing Chen; Mu-Xuan Tao (Engineering Structures, 2024)

The Relationships Between Danxia Geoheritages and Regional Tectonics in Southern Sichuan Basin: Implications for the Spatial Distribution of Danxia Landforms in China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yan-Jie Yang; Pengju Li; Liang Qiu; Chao-Bin Xu (Geoheritage, 2024)

Regulation and mechanism of pyrite and humic acid on the toxicity of arsenate in lettuce - Jingyu Wen; Xin Tang; Mengyuan Wang; Li Mu; Weidan Hao; Jingxian Weng; Ziwei Gao; Xiangang Hu (Science of The Total Environment, 2024)

BioTreasury: a community-based repository enabling indexing and rating of bioinformatics tools - Qi Zhao; Xin Zhou; Jingxing Wu; Jieyi Cai; Xiaoqiong Bao; Lin Tang; Chaoye Wang; Chunlei Liu; Yukai Wang; Yuyan Teng; Mohan Zheng; Weiping Mu; et al. (Science China Life Sciences, 2024)

Construction of and evaluation of the immune response to two recombinant pseudorabies viruses expressing the B119L and EP364R proteins of African swine fever virus - Xin-Mei Geng; Ying-Mu Xi; Xiang-Mei Huang; Yang-Lin Wang; Xu-Ying Wang; Kang Ouyang; Ying Chen; Zu-Zhang Wei; Yi-Feng Qin; Wei-Jian Huang (Archives of Virology, 2024)

Hydrothermal carbonization of coking sludge: Formation mechanism and fuel characteristic of hydrochar - Jun Zhong; Wei Zhu; Jipeng Sun; Biao Mu; Xin Wang; Zongpu Xue; Jun Cao (Chemosphere, 2024)

Biogeography and diversity patterns of functional genes associated with C, N, P, S cycling processes across China classical sea sediments - Shuai Liu; Xin Huang; Hongyu Mu; Minggang Zheng; Shaoping Kuang; Hui Chen; Yan Xu; Dong Wang; Huan Liu; Xuan Li (Science of The Total Environment, 2024)

A Critical Review of On-Line Oil Wear Debris Particle Detection Sensors - Wenbo Han; Xiaotong Mu; Yu Liu; Xin Wang; Wei Li; Chenzhao Bai; Hongpeng Zhang (Journal of Marine Science and Engineering, 2023)
In the field of marine engineering, the friction and wear experienced by rotating mechanisms are recognized as significant contributors to the failure of marine machinery. In order to enhance the safety and dependability of marine ship operations, the implementation of on-line oil wear debris particle detection sensors enables the on-line monitoring of oil and facilitates the rapid identification of abnormal wear locations. This paper provides a critical review of the recent research progress and development trends in the field of sensors for on-line detection of oil wear debris particles. According to the method of sensor detection, wear debris particle detection sensors can be classified into two distinct categories: electrical and non-electrical sensors. Electrical sensors encompass a range of types, including inductive, capacitive, and resistive sensors. Non-electrical sensors encompass a range of technologies, such as image processing sensors, optical sensors, and ultrasonic sensors. Finally, this review addresses the future research directions for wear debris particle detection sensors in light of the challenging problems currently faced by these sensors.

A comprehensive observation on the pollution characteristics of peroxyacetyl nitrate (PAN) in Beijing, China - Hailiang Zhang; Shengrui Tong; Wenqian Zhang; Yanyong Xu; Mingzhu Zhai; Yucong Guo; Xin Li; Lili Wang; Guiqian Tang; Zirui Liu; Bo Hu; Chengtang Liu; et al. (Science of The Total Environment, 2023)

Improved solid/liquid separation performance of hydrochar from sludge via hydrothermal carbonization - Jun Zhong; Wei Zhu; Biao Mu; Jipeng Sun; Xin Wang; Naixi Lin; Jun Cao (Journal of Environmental Management, 2023)

Waterborne polyurethanes with novel chain extenders bearing multiple sulfonate groups - Guozheng Xia; Jinkang Hu; Qian Sun; Chi Chen; Xin Wang; Chao Zhu; Wei Jiang; Xiaobo Wan; Youbing Mu (Chemical Engineering Journal, 2023)

Elucidation of the neutralizing antibody evasion of emergent SARS-CoV-2 Omicron sub-lineages using structural analysis - Cong Sun; Yuan-Tao Liu; Yin-Feng Kang; Chu Xie; Shu-Xin Li; Yu-Tong Lu; Mu-Sheng Zeng (Science China Life Sciences, 2023)

Targeting mitophagy for neurological disorders treatment: advances in drugs and non-drug approaches - Xiong Yang; Yu Zhang; Jia-xin Luo; Tao Zhu; Zhao Ran; Ben-Rong Mu; Mei-Hong Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Lidocaine pretreatment attenuates inflammatory response and protects against sepsis-induced acute lung injury via inhibiting potassium efflux-dependent NLRP3 activation - Kai Su; Xin-Tao Li; Fang-Xiao Hong; Mu Jin; Fu-Shan Xue (Inflammation Research, 2023)

Construction of a xylose metabolic pathway in Trichosporonoides oedocephalis ATCC 16958 for the production of erythritol and xylitol - Zhou Deng; Yinghui Mu; Zhi Chen; Lishi Yan; Xin Ju; Liangzhi Li (Biotechnology Letters, 2023)

Cerina litoralis gen. nov., sp. nov., a novel potential polysaccharide degrading bacterium of the family Flavobacteriaceae, isolated from marine sediment - Ya-Wei Wang; Xin-Hui Wang; Jing Zhang; Zong-Jun Du; Da-Shuai Mu (Antonie van Leeuwenhoek, 2023)

Exposure to phthalates and their alternatives in relation to biomarkers of inflammation and oxidative stress in adults: evidence from NHANES 2017–2018 - Shihao Jin; Shanshan Cui; Xiaoyu Mu; Zhao Liu; Yu Han; Tingkai Cui; Wenjuan Xiong; Wei Xi; Xin Zhang (Environmental Science and Pollution Research, 2023)

Effect mechanism of iron conversion on adsorption performance of hydrochar derived from coking sludge - Jun Zhong; Wei Zhu; Xin Wang; Jipeng Sun; Biao Mu; Yucheng Xu; Guorui Li (Science of The Total Environment, 2023)

Optimizing flow regime for the Four Major Chinese Carps by integrating habitat suitability within reservoir operation - Zehao Lv; Gangsheng Wang; Peng Zhang; Xueshan Ai; Xin Cao; Wei Zheng; Zhenyu Mu; Bowen Yu (Journal of Hydrology, 2023)

Community composition, co-occurrence, and environmental drivers of bacterioplankton community in surface and 50-m water layers in the subarctic North Pacific - Quandong Xin; Jufa Chen; Changkao Mu; Xinliang Wang; Wenjing Liu; Tao Jiang; Yan Li (Journal of Oceanology and Limnology, 2023)

Improving the yield and tetracycline adsorption performance of kitchen waste biochar through subcritical dimethyl ether pretreatment - Jipeng Sun; Wei Zhu; Jun Cao; Jun Zhong; Biao Mu; Xin Wang; Naixi Lin (Journal of Environmental Chemical Engineering, 2023)

Emission factors and source profiles of VOCs emitted from coke production in Shanxi, China - Ling Mu; Chuanyang Feng; Yangyong Li; Xiaofan Li; Tian Liu; Xin Jiang; Ziye Liu; Huiling Bai; Xiaofeng Liu (Environmental Pollution, 2023)

Self-healing polyurethane coatings based on dynamic chemical bond synergy under conditions of photothermal response - Kang Chen; Haoxin Zhu; Zhiyi Zhang; Yingqing Shao; Qianhui Yu; Xinlei Cao; Siyan Pan; Xin Mu; Zhenhua Gao; Di Wang; Shuangying Wei; Shuaiyuan Han (Chemical Engineering Journal, 2023)

Biological neutralization of bauxite residue with fermented waste sludge and bio-acid, and the microbial ecological restoration - Dainan Qin; Xiaotong Tan; Xin Zhao; Lulu Qian; Yuanyuan Nie; Xiaolin Pan; Qun Gao; Mu Peng; Yang Liu; Xiaoyu Han (Chemical Engineering Journal, 2023)

Molecular mechanism by which StSN2 overexpression inhibits the enzymatic browning of potato - Li-qin Li; Yu-lu Mu; Jing Chen; Qiang Wang; Yi-fei Lu; Sun Xin; Shi-min Yang; Xue-li Huang; Xi-yao Wang; Li-ming Lu (Postharvest Biology and Technology, 2023)

C21 steroids from the roots of Marsdenia tenacissima - Jin-Ling Liu; Hong-Tao Xu; Dan-Dan Mu; Xiao Han; Ting-Ting Du; Yong-li Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

Maternal exposure to cetylpyridinium chloride impairs oogenesis by causing mitochondria disorder in neonates - Ronglu Liu; Xinyi Mu; Rufei Gao; Yanqing Geng; Yan Zhang; Xuemei Chen; Xin Yin; Hong Wang; Fangfang Li; Junlin He (Environmental Toxicology and Pharmacology, 2023)

Electricity facilitates the lithium sorption from salt-lake brine by H3LiTi5O12 nanoparticles: Kinetics, selectivity and mechanism - Qiuyue Wang; Mu Li; Bing Zhao; Boyang Meng; Wutong Chen; Zekai Jiang; Xin He; Bing Li; Xiao-yan Li; Lin Lin (Chemical Engineering Journal, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Synergistic generation mechanisms of SOA and ozone from the photochemical oxidation of 1,3,5-trimethylbenzene: Influence of precursors ratio, temperature and radiation intensity - Hao Zhang; Hong Li; Yujie Zhang; Xuezhong Wang; Fang Bi; Lingshuo Meng; Yunfeng Li; Lu Zhao; Xin Zhang; Zhijian Peng; Yujing Mu; Wahid Mellouki; et al. (Atmospheric Research, 2023)

Maternal exposure to dibutyl phthalate regulates MSH6 crotonylation to impair homologous recombination in fetal oocytes - Yidan Ma; Xinyi Mu; Rufei Gao; Yan Zhang; Yanqing Geng; Xuemei Chen; Xin Yin; Fangfang Li; Junlin He (Journal of Hazardous Materials, 2023)

Simultaneous dissolution of nickel, copper and cobalt from low grade nickel matte by (NH4)2S2O8-H2SO4 oxidative leaching - Wenning Mu; Peng Zhong; Mengfei Gu; Weisong Sun; Tengfei Xiao; Hongtao Shen; Haixia Xin; Xuefei Lei; Shaohua Luo; Le Wang (Hydrometallurgy, 2023)

Understanding the digestibility of wheat starch- caffeic acid complexes prepared by hot-extrusion 3D printing technology - Xin-Ru Cui; Yu-Sheng Wang; Yan Chen; Hong-Yan Mu; Hai-Hua Chen (Food Hydrocolloids, 2023)

Impacts of cold-extrusion whey protein isolate synergized with inulin on physicochemical characteristics of fermented milk - Hongyu Li; Jialu Sun; xin Mu; Munkh-Amgalan Gantumur; Xianqi Liu; Jinpeng Li; Sinan Mu; Minghan Zhang; Zhanmei Jiang; Hui Tian (Food Bioscience, 2023)

Delamination of multilayer Ti3C2T MXene alters its adsorpiton and reduction of heavy metals in water - Yuxuan Zhang; Jun Luo; Biao Feng; Hongxia Xu; Yuanyuan Sun; Xueyuan Gu; Xin Hu; Mu Naushad; Bin Gao; Hongqiang Ren (Environmental Pollution, 2023)

Distribution characteristics of secondary organic aerosol tracers in PM2.5 in Jinzhong - Ling Mu; Xin Jiang; Yangyong Li; Xuemei Li; Xiaofan Li; Tian Liu; Ziye Liu; Chuanyang Feng (Atmospheric Environment, 2023)

Salinilacihabitans rarus gen. nov., sp. nov., Natrononativus amylolyticus gen. nov., sp. nov., Natronobeatus ordinarius gen. nov., sp. nov., and Halovivax gelatinilyticus sp. nov., halophilic archaea, isolated from a salt lake and soda lakes - Xin-Xin Li; Shun Tan; Mu Cheng; Yao Hu; Xue Ma; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Eugenilones A−N: sesquiterpenoids from the fruits of Eugenia uniflora - Mu Chen; Run-Qiang Chen; Yuan Guo; Jian-Xin Chen; Qian Jin; Mei-Hong Chen; Bo-Yong Chen; Zheng-Chao Tu; Wen-Cai Ye; Lei Wang (Phytochemistry, 2023)

Characteristics and source apportionment of water-soluble inorganic ions in atmospheric particles in Lvliang, China - Tian Liu; Ling Mu; Xiaofan Li; Yangyong Li; Ziye Liu; Xin Jiang; Chuanyang Feng; Lirong Zheng (Environmental Geochemistry and Health, 2023)

Regulation of arsenite toxicity in lettuce by pyrite and glutamic acid and the related mechanism - Xin Tang; Jingyu Wen; Li Mu; Ziwei Gao; Jingxian Weng; Xiaokang Li; Xiangang Hu (Science of The Total Environment, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Size-controllable Rh2P nanoparticles on reduced graphene oxide toward highly hydrogen production - Hongqiang Xin; Lan Sun; Yiwei Zhao; Yuanjiang Lv; Qiaomei Luo; Shengwu Guo; Danyang Li; Ce Mu; Bo Huang; Fei Ma (Chemical Engineering Journal, 2023)

Membrane with horizontally rigid zeolite nanosheet arrays against zinc dendrites in zinc-based flow battery - Yongsheng Xia; Xiaoxuan Hou; Xinyi Chen; Feiyan Mu; Yan Wang; Liheng Dai; Xin Liu; Ying Yu; Kang Huang; Weihong Xing; Zhi Xu (Chemical Engineering Journal, 2023)

A seminal perspective on the role of chondroitin sulfate in biomineralization - Jia-xin Hao; Qian-qian Wan; Zhao Mu; Jun-ting Gu; Wei-wei Yu; Wen Qin; Yu-tao Li; Chen-yu Wang; Yu-xuan Ma; Kai Jiao; Franklin Tay; Lina Niu (Carbohydrate Polymers, 2023)

Dysfunction of NRG1/ErbB4 Signaling in the Hippocampus Might Mediate Long-term Memory Decline After Systemic Inflammation - Yu-zhu Gao; Xin-miao Wu; Zhi-qiang Zhou; Pan-miao Liu; Jian-jun Yang; Mu-huo Ji (Molecular Neurobiology, 2023)

Ecotoxicological risk assessment of 14 pesticides and corresponding metabolites to groundwater and soil organisms using China-PEARL model and RQ approach - Jiangong Jiang; Zhixin Liu; Beixing Li; Shankui Yuan; Ronghua Lin; Xin Yu; Xiao Liu; Xianxia Zhang; Ke Li; Dong Xiao; Shaoli Yu; Wei Mu (Environmental Geochemistry and Health, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Inducing itinerant ferromagnetism by manipulating van Hove singularity in epitaxial monolayer 1T-VSe2 - Junyu Zong; Zhao-Yang Dong; Junwei Huang; Kaili Wang; Qi-Wei Wang; Qinghao Meng; Qichao Tian; Xiaodong Qiu; Yuyang Mu; Li Wang; Wei Ren; Xuedong Xie; et al. (Science Bulletin, 2023)

Investigation on the formation mechanism of main products from TBBPA pyrolysis using DFT method - Xin Mu; Yao Wang; Jinbao Huang; Lin Lan; Hong Wang; Weiwei Xu; Xinsheng Li (Chemosphere, 2023)

Dissecting LuxS/AI-2 quorum sensing system-mediated phenyllactic acid production mechanisms of Lactiplantibacillus plantarum L3 - Yunmei Chai; Qingwen Ma; Xin Nong; Xinyue Mu; Aixiang Huang (Food Research International, 2023)

Modification of sedimentation and bioaccumulation behavior as an efficient strategy to modulate the toxicity of pyraclostrobin to zebrafish (Danio rerio) - Aiping Wang; Yue Sun; Zhengyi Sun; Xiao Liu; Xin Yu; Ke Li; Xianxia Zhang; Yue Xu; Wei Mu; Beixing Li (Environmental Pollution, 2023)

Natrinema caseinilyticum sp. nov., Natrinema gelatinilyticum sp. nov., Natrinema marinum sp. nov., Natrinema zhouii sp. nov., extremely halophilic archaea isolated from marine environments and a salt mine - Yao Hu; Xue Ma; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

A novel nanoparticle surface-constrained CRISPR-Cas12a 3D DNA walker-like nanomachines for sensitive and stable miRNAs detection - Xin Wang; Xiaomei Mu; Jinshen Li; Guang Liu; Shulin Zhao; Jianniao Tian (Analytica Chimica Acta, 2023)

Canopy greenness, atmospheric aridity, and large rain events jointly regulate evapotranspiration partitioning in a temperate semiarid shrubland - Shaorong Hao; Xin Jia; Yanmei Mu; Tianshan Zha; Shugao Qin; Peng Liu; Yun Tian; Jiandong Qi; Hongxian Zhao; Xinhao Li (Agricultural and Forest Meteorology, 2023)

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

Multi-objective combinatorial optimization analysis of the recycling of retired new energy electric vehicle power batteries in a sustainable dynamic reverse logistics network - Nengye Mu; Yuanshun Wang; Zhen-Song Chen; Peiyuan Xin; Muhammet Deveci; Witold Pedrycz (Environmental Science and Pollution Research, 2023)

Liquid metal @ mxene spring supports ionic gel with excellent mechanical properties for high-sensitivity wearable strain sensor - Lisong Dong; Xiaoyao Zhou; Shuxin Zheng; Zhongfan Luo; Yuxiang Nie; Xin Feng; Jiahua Zhu; Zhangzhong Wang; Xiaohua Lu; Liwen Mu (Chemical Engineering Journal, 2023)

New (4 → 2)-abeo-clerodane diterpenoids from the Polyalthia laui and their chemotaxonomic significance - Zhang-Xin Yu; Xin-Ming Song; Mu-Yuan Li; Man-Man Zhang; Li-Zhu Huang; Xiao-Bao Li (Biochemical Systematics and Ecology, 2023)

Phytoplankton community structure in the Western Subarctic Gyre of the Pacific Ocean during summer determined by a combined approach of HPLC-pigment CHEMTAX and metabarcoding sequencing - Quandong Xin; Xiaohan Qin; Guannan Wu; Xiaokun Ding; Xinliang Wang; Qingjing Hu; Changkao Mu; Yuqiu Wei; Jufa Chen; Tao Jiang (Frontiers in Marine Science, 2023)
The Western Subarctic Gyre (WSG) is a cyclonic upwelling gyre in the northwest subarctic Pacific, which is a region with a high concentration of nutrients but low chlorophyll. We investigated the community structure and spatial distribution of phytoplankton in this area by using HPLC-pigment CHEMTAX (a chemotaxonomy program) and metabarcoding sequencing during the summer of 2021. The phytoplankton community showed significant differences between the two methods. The CHEMTAX analyses identified eight major marine phytoplankton assemblages. Cryptophytes were the major contributors (24.96%) to the total Chl a , followed by pelagophytes, prymnesiophytes, diatoms, and chlorophytes. The eukaryotic phytoplankton OTUs obtained by metabarcoding were categorized into 149 species in 96 genera of 6 major groups (diatoms, prymnesiophytes, pelagophytes, chlorophytes, cryptophytes, and dinoflagellates). Dinoflagellates were the most abundant group, accounting for 44.74% of the total OTUs obtained, followed by cryptophytes and pelagophytes. Sixteen out of the 97 identified species were annotated as harmful algal species, and Heterocapsa rotundata , Karlodinium veneficum , and Aureococcus anophagefferens were assigned to the abundant group (i.e., at least 0.1% of the total reads). Nutrients were more important in shaping the phytoplankton community than temperature and salinity. The 24 stations were divided into southern and northern regions along 44°N according to the k -means method, with the former being dominated by high Chl a and low nutrients. Although different phytoplankton assemblages analyzed by the two methods showed various relationships with environmental factors, a common feature was that the dinoflagellate proportion showed a significantly negative correlation with low nutrients and a positive correlation with Chl a .

Theoretical study on pyrolysis mechanism of decabromodiphenyl ether (BDE-209) using DFT method - Yao Wang; Jinbao Huang; Hong Wang; Lin Lan; Xin Mu; Weiwei Xu; Shanjin Lv; Xinsheng Li (Chemosphere, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Ambient volatile organic compounds in urban and industrial regions in Beijing: Characteristics, source apportionment, secondary transformation and health risk assessment - Chengtang Liu; Yanyan Xin; Chenglong Zhang; Junfeng Liu; Pengfei Liu; Xiaowei He; Yujing Mu (Science of The Total Environment, 2023)

High-efficient and recoverable Mo72V30@Fe3O4/C catalyst for oxidation of hydroxyfurfural - Mengdi Gong; Xin-Yu Wang; Mu-Qin Li; Wen-Xia Mu; Yun-Dong Cao; Hong Liu; Yu-Guang Lv; Xin-Hua Qi; Guang-Gang Gao (Fuel, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Study on the deactivation mechanism of HZSM-5 in the process of catalytic cracking of n-hexane - Mu He; Muhammad-Faryad Ali; Yue-Qin Song; Xiao-Long Zhou; Jin An Wang; Xin-Yao Nie; Zheng Wang (Chemical Engineering Journal, 2023)

Geochemical evolution of structure-bedding controlled hydrothermal dolomites of the Kinta Valley, Western Malaysia - P. Xin Hui; R. Nagarajan; Mu. Ramkumar; T. F. Ng; Nur I. Taib; M. J. Mathew; B. Sautter; N. A. Siddiqui; M. C. Poppelreiter (Carbonates and Evaporites, 2022)
Study of secondary dolomitization and documentation of the evolution of basinal fluids and host rock, especially that of fine-grained deepwater carbonate mudstone are of interest toward of reservoir characterization. From this perspective, field characteristics in relation to mineralogy, petrography and geochemistry of the Paleaozoic carbonates of the Kinta Valley, Peninsular Malaysia, were investigated and documented. A total of 33 samples were collected across the various degree of dolomitization and analyzed for their petrographic properties ( n = 55), while mineralogical and geochemical compositions ( n = 33) were analyzed using XRD, ICP and ICPMS analysis, respectively. These analyses were performed to elucidate the diagenetic events, episodic dolomitization and development of fluid evolution as a function of regional tectono-thermal events during the Permian to Cenozoic. It is interpreted that the host calcareous mudstones (HCMs) were deposited in oxygenated, open marine seawaters. The studied samples retain the original seawater characteristics despite negligible, minor alterations of REE characteristics due to diagenesis and detrital input. Though the concentrations and trends of REEs of the dolomitic facies are modified to a certain extent, their affinities with HCMs are preserved. Enrichments of Mg, Mn, Na and depletion of Sr are linked to the effect of dolomitization under the open system of diagenesis. The redox conditions fluctuated to show distinct, recognizable variations between different dolomite phases. The MREE enrichments with other trace elements such as Mn, Fe and low Sr content indicate the association of diagenetic fluids with deep-circulating crustal hydrothermal fluids. Hydrothermal influence has been recorded along the fractures, which might have originated from the sub-surface litho units and facilitated episodic dolomitization, especially during significant tectono-thermal events. This study affirms that the occurrence, geochemical and mineralogical evolution of the dolomites of the Kinta Valley were controlled by magmatic events, whereas the intensity of replacement dolomitization was controlled by host rock texture, varied bulk chemistry of host rock, circulating fluid and temperature.

Predation capacity of Bradymonabacteria, a recently discovered group in the order Bradymonadales, isolated from marine sediments - Ya Gong; Xiu-Ya Ping; Chen-Hang Zeng; Shu-Xin Wang; Yi Zhou; Ming-Yi Wang; Da-Shuai Mu; Zong-Jun Du (Archives of Microbiology, 2022)

Deoxynivalenol induces caspase-3/GSDME-dependent pyroptosis and inflammation in mouse liver and HepaRG cells - Xiaoxiao Mao; Jie Li; Xin Xie; Shuang Chen; Qiang Huang; Peiqiang Mu; Jun Jiang; Yiqun Deng (Archives of Toxicology, 2022)

A Variational Bayesian-Based Simultaneous Localization and Mapping Method for Autonomous Underwater Vehicle Navigation - Pengcheng Mu; Xin Zhang; Ping Qin; Bo He (Journal of Marine Science and Engineering, 2022)
Simultaneous Localization and Mapping (SLAM) is a well-known solution for mapping and realizing autonomous navigation of an Autonomous Underwater Vehicle (AUV) in unknown underwater environments. However, the inaccurate time-varying observation noise will cause filtering divergence and reduce the accuracy of localization and feature estimation. In this paper, VB-AUFastSLAM based on the unscented-FastSLAM (UFastSLAM) and the Variational Bayesian (VB) is proposed. The UFastSLAM combines unscented particle filter (UPF) and unscented Kalman filter (UKF) to estimate the AUV poses and features. In addition, to resist the unknown time-varying observation noise, the method of Variational Bayesian learning is introduced into the SLAM framework. Firstly, the VB method is used to estimate the joint posterior probability of the AUV path and observation noise. The Inverse-Gamma distribution is used to model the observation noise and real-time noise parameters estimation is performed to improve the AUV localization accuracy. Secondly, VB is reused to estimate the noise parameters in the feature update stage to enhance the performance of the feature estimation. The proposed algorithms are first validated in an open-source simulation environment. Then, an AUV SLAM system based on the Inertial Navigation System (INS), Doppler Velocity Log (DVL), and single-beam Sonar are also built to verify the effectiveness of the proposed algorithms in the marine environment. The accuracy of the proposed methods can reach 0.742% and 0.776% of the range, respectively, which is much better than 1.825% and 1.397% of the traditional methods.

Two new alkaloids from Tibetan medicine of Hypecoum leptocarpum - Bo Sun; Israa Assani; Chun-Gu Wang; Mu-Xuan Wang; Ling-Fei Liu; Yan Li; Ge Yan; Yun-Ruo Yang; Zhi Chen; Zhi-Xin Liao (Natural Product Research, 2022)

Effects of tillage and cropping sequences on crop production and environmental benefits in the North China Plain - Wen-Xuan Liu; Wen-Sheng Liu; Mu-Yu Yang; Yu-Xin Wei; Zhe Chen; Ahmad Latif Virk; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Environmental Science and Pollution Research, 2022)

Efficient degradation of semi-coking wastewater in three-dimensional electro-Fenton by CuFe2O4 heterocatalyst - Wen-wen Gao; Ting Su; Wei Zhao; Zhi-fang Zhang; Miao Mu; Yong-hui Song; Xue-xue Zhang; Xin-yu Liu (Environmental Science and Pollution Research, 2022)

Physiological and Molecular Analyses of Low-Salinity Stress Response in the Cuttlefish (Sepia pharaonis) Juveniles - Hongwei Xin; Kunlan Wu; Yimeng Yuan; Yun Zhao; Weiwei Song; Chunlin Wang; Changkao Mu; Ronghua Li (Journal of Ocean University of China, 2022)

Associations between species-level indoor microbiome, environmental characteristics, and asthma in junior high schools of Terengganu, Malaysia - Xi Fu; Yi Meng; Yanling Li; Xunhua Zhu; Qianqian Yuan; Aminnuddin Ma’pol; Jamal Hisham Hashim; Zailina Hashim; Gunilla Wieslander; Yi-Wu Zheng; Xu-Xin Lai; Michael Dho Spangfort; et al. (Air Quality, Atmosphere & Health, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Psychroserpens luteolus sp. nov., isolated from Gelidium, reclassification of Ichthyenterobacterium magnum as Psychroserpens magnus comb. nov., Flavihalobacter algicola as Psychroserpens algicola comb. nov., Arcticiflavibacter luteus as Psychroserpens luteus comb. nov - Xiu-Ya Ping; Kai Wang; Jin-Yu Zhang; Shu-Xin Wang; Zong-Jun Du; Da-Shuai Mu (Archives of Microbiology, 2022)

Seismic behavior of precast segmental column bridges under near-fault forward-directivity ground motions - Xin Lifeng; Li Xiaozhen; Fu Peiyao; Mu Di (Earthquake Engineering and Engineering Vibration, 2022)

Recent advances on 2′-fucosyllactose: physiological properties, applications, and production approaches - Yingying Zhu; Li Wan; Wen Li; Dawei Ni; Wenli Zhang; Xin Yan; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2022)

RETRACTED ARTICLE: Evaluating an economic application of renewable generated hydrogen: A way forward for green economic performance and policy measures - Baijun Wu; Bingfeng Zhai; Huaizi Mu; Xin Peng; Chao Wang; Ataul Karim Patwary (Environmental Science and Pollution Research, 2022)

DFT studies on pyrolysis mechanisms of tetrabromobisphenol A (TBBPA) - Jinbao Huang; Xin Mu; Xiaosong Luo; Hanxian Meng; Hong Wang; Li Jin; Xinsheng Li; Baosheng Lai (Environmental Science and Pollution Research, 2021)

Sea level anomaly intelligent inversion model based on LSTM-RBF network - Hanmin Liu; Bo He; Ping Qin; Xin Zhang; Shuai Guo; Xiaokai Mu (Meteorology and Atmospheric Physics, 2021)

Freeze-thaw resistance of eco-material stabilized loess - Guo-yu Li; Xin Hou; Yu Zhou; Wei Ma; Yan-hu Mu; Dun Chen; Li-yun Tang (Journal of Mountain Science, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

The anti-inflammatory drug dimethyl itaconate protects against colitis-associated colorectal cancer - Qian Wang; Xin Ling Li; Yan Mei; Jia-Chong Ye; Wei Fan; Guang-Hui Cheng; Mu-Sheng Zeng; Guo-Kai Feng (Journal of Molecular Medicine, 2020)

Dissection and validation of a QTL cluster linked to Rht-B1 locus controlling grain weight in common wheat (Triticum aestivum L.) using near-isogenic lines - Panfeng Guan; Xueyi Shen; Qing Mu; Yongfa Wang; Xiaobo Wang; Yongming Chen; Yue Zhao; Xiyong Chen; Aiju Zhao; Weiwei Mao; Yiwen Guo; Mingming Xin; et al. (Theoretical and Applied Genetics, 2020)

The Activation of Heat-Shock Protein After Copper(II) and/or Arsenic(III)-Induced Imbalance of Homeostasis, Inflammatory Response in Chicken Rectum - Xin Yang; Hongjing Zhao; Yu Wang; Juanjuan Liu; Menghao Guo; Dongxue Fei; Mengyao Mu; Mingwei Xing (Biological Trace Element Research, 2020)

Pure qP-wave least-squares reverse time migration in vertically transverse isotropic media and its application to field data - Jian-Ping Huang; Xin-Ru Mu; Zhen-Chun Li; Qing-Yang Li; Shuang-Qi Yuan; Yun-Dong Guo (Applied Geophysics, 2020)

Elemental imbalance elicited by arsenic and copper exposures leads to oxidative stress and immunotoxicity in chicken gizzard, activating the protective effects of heat shock proteins - Menghao Guo; Hongjing Zhao; Yu Wang; Juanjuan Liu; Dongxue Fei; Xin Yang; Mengyao Mu; Mingwei Xing (Environmental Science and Pollution Research, 2019)

Engineering properties of loess stabilized by a type of eco-material, calcium lignosulfonate - Guo-yu Li; Xin Hou; Yan-hu Mu; Wei Ma; Fei Wang; Yu Zhou; Yun-cheng Mao (Arabian Journal of Geosciences, 2019)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

Fine-mapping and transcriptome analysis of BoGL-3, a wax-less gene in cabbage (Brassica oleracea L. var. capitata) - Xin Dong; Jialei Ji; Limei Yang; Zhiyuan Fang; Mu Zhuang; Yangyong Zhang; Honghao Lv; Yong Wang; Peitian Sun; Jun Tang; Dongming Liu; Yumei Liu; et al. (Molecular Genetics and Genomics, 2019)

Geosites in Karamay city, Xinjiang Uygur Autonomous Region, northwest China - Jun-Ting Qiu; Liang Qiu; Hong-Xu Mu; Wen-Xin Yang; Feng Chen; Bo-Kun Yan; Jun-Chuan Yu; He-Ming Yang (Geoheritage, 2019)

Use of near-isogenic lines to precisely map and validate a major QTL for grain weight on chromosome 4AL in bread wheat (Triticum aestivum L.) - Panfeng Guan; Na Di; Qing Mu; Xueyi Shen; Yongfa Wang; Xiaobo Wang; Kuohai Yu; Wanjun Song; Yongming Chen; Mingming Xin; Zhaorong Hu; Weilong Guo; et al. (Theoretical and Applied Genetics, 2019)

Astaxanthin enhances hematology, antioxidant and immunological parameters, immune-related gene expression, and disease resistance against in Channa argus - Mu-Yang Li; Xin-Yu Liu; Chang-Ge Xia; Gui-Qin Wang; Dong-Ming Zhang (Aquaculture International, 2019)

Effects of dietary Allium mongolicum Regel polysaccharide on growth, lipopolysaccharide-induced antioxidant responses and immune responses in Channa argus - Mu-Yang Li; Xin-Ming Zhu; Xiao-Tian Niu; Xiu-Mei Chen; Jia-Xin Tian; Yi-Di Kong; Dong-Ming Zhang; Lei Zhao; Gui-Qin Wang (Molecular Biology Reports, 2019)

Tilapia fisheries in Guangdong Province, China: Socio‐economic benefits, and threats on native ecosystems and economics - Dang En Gu; Fan Dong Yu; Ye Xin Yang; Meng Xu; Hui Wei; Du Luo; Xi Dong Mu; Yin Chang Hu (Fisheries Management and Ecology, 2019)
Tilapia is one of the groups of fish species most widely cultured globally. China has been the largest producer of tilapia in the world since 1990s. Guangdong Province produces almost 40% of all tilapia in China because of its suitable geography and weather conditions, and tilapia culture has brought considerable economic benefits. Unfortunately, many of the biological traits that make tilapia popular for culture also contribute to its success as an invader. Tilapia has invaded natural waters and has become the dominant fish in many rivers of Guangdong Province, causing economic loss in capture fisheries, and affecting native fish species, biodiversity and aquatic ecosystems. Poor fishery management, water quality degradation and biodiversity loss have all facilitated the tilapia invasion. Tilapia have filled the niches left vacant by now locally extinct native species resulting from environmental changes in freshwater ecosystems of the province. The introduction of tilapia has both advantages and disadvantages, which should be managed to use effectively the various tilapia species in aquaculture while controlling their spread in natural waters.

The complete maternal mitochondrial genome sequence of Cuneopsis heudei (Bivalvia: Unionoida: Unionidae) - Qishuo Wang; Lu Ma; Lin Li; Ruijuan Feng; Huan Mu; Xin Wang; Cheng Wang; Xuepeng Wang (Conservation Genetics Resources, 2018)

Early Mesozoic magmatism and tectonic evolution of east-central Tibet - Yanfei Chen; Zeming Zhang; Zuolin Tian; Xin Dong; Huixia Ding; Hongchen Mu; Dongyan Kang; Yunshuai Li (International Journal of Earth Sciences, 2018)

High-Temperature Metamorphism, Anataxis and Tectonic Evolution of a Mafic Granulite from the Eastern Himalayan Orogen - Zeming Zhang; Huixia Ding; Xin Dong; Zuolin Tian; Dongyan Kang; Hongchen Mu; Shengkai Qin; Yuanyuan Jiang; Mengmei Li (Journal of Earth Science, 2018)

Efficient Using Durian Shell Hydrolysate as Low-Cost Substrate for Bacterial Cellulose Production by Gluconacetobacter xylinus - Mu-Tan Luo; Cheng Zhao; Chao Huang; Xue-Fang Chen; Qian-Lin Huang; Gao-Xiang Qi; Lan-Lan Tian; Lian Xiong; Hai-Long Li; Xin-De Chen (Indian Journal of Microbiology, 2017)

RHEB1 insufficiency in aged male mice is associated with stress-induced seizures - Qi Tian; Pavel Gromov; Joachim H. Clement; Yingming Wang; Marc Riemann; Falk Weih; Xiao-Xin Sun; Mu-Shui Dai; Lev M. Fedorov (GeroScience, 2017)

Long-term perceptions of outdoor thermal environments in an elementary school in a hot-humid climate - Wen-Mei Shih; Tzu-Ping Lin; Ning-Xin Tan; Mu-Hsien Liu (International Journal of Biometeorology, 2017)

Trade-offs between carbon sequestration, soil retention and water yield in the Guanzhong-Tianshui Economic Region of China - Xiaonan Yang; Zixiang Zhou; Jing Li; Xin Fu; Xingmin Mu; Ting Li (Journal of Geographical Sciences, 2016)

Propofol Prevents Hippocampal Neuronal Loss and Memory Impairment in Cerebral Ischemia Injury Through Promoting PTEN Degradation - Xin Chen; Ye-Mu Du; Feng Xu; Dai Liu; Yuan-Lin Wang (Journal of Molecular Neuroscience, 2016)

A graphical model for haloanhydrite components and P-wave velocity: A case study of haloanhydrites in Amu Darya Basin - Tong-Cui Guo; Hong-Jun Wang; Long-Xin Mu; Xing-Yang Zhang; Zhi Ma; Yu Tian; Hao-Chen Li (Applied Geophysics, 2016)

A characterization of grapevine of GRAS domain transcription factor gene family - Xin Sun; Zhengqiang Xie; Cheng Zhang; Qian Mu; Weimin Wu; Baoju Wang; Jinggui Fang (Functional & Integrative Genomics, 2016)

Water Storage Changes over the Tibetan Plateau Revealed by GRACE Mission - Jinyun Guo; Dapeng Mu; Xin Liu; Haoming Yan; Zhongchang Sun; Bin Guo (Acta Geophysica, 2016)

Comparison and verification of the genes involved in ethylene biosynthesis and signaling in apple, grape, peach, pear and strawberry - Mu Qian; Wang Baoju; Leng Xiangpeng; Sun Xin; Shangguan Lingfei; Jia Haifeng; Fang Jinggui (Acta Physiologiae Plantarum, 2016)

Catalpol Inhibited the Proliferation of T24 Human Bladder Cancer Cells by Inducing Apoptosis Through the Blockade of Akt-Mediated Anti-apoptotic Signaling - Di Jin; Ming Cao; Xin Mu; Guoliang Yang; Wei Xue; Yiran Huang; Haige Chen (Cell Biochemistry and Biophysics, 2015)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

SNAP25 Ameliorates Sensory Deficit in Rats with Spinal Cord Transection - Wei Wang; Fang Wang; Jia Liu; Wei Zhao; Qi Zhao; Mu He; Bao-Jiang Qian; Yang Xu; Ran Liu; Su-Juan Liu; Wei Liu; Jin Liu; et al. (Molecular Neurobiology, 2014)

Equivalent water height extracted from GRACE gravity field model with robust independent component analysis - Jinyun Guo; Dapeng Mu; Xin Liu; Haoming Yan; Honglei Dai (Acta Geophysica, 2014)

Molecular cloning and characterization of the promoter region of the porcine apolipoprotein E gene - Jihan Xia; Bingjun Hu; Yulian Mu; Leilei Xin; Shulin Yang; Kui Li (Molecular Biology Reports, 2014)

An Informetric Profile of Water Resources Management Literatures - Jun-Lin Ren; Peng-Hui Lyu; Xin-Mu Wu; Fei-Cheng Ma; Zhi-Zhang Wang; Gang Yang (Water Resources Management, 2013)

Prelog and anti-Prelog stereoselectivity of two ketoreductases from Candida glabrata - Ping Liang; Bin Qin; Mao Mu; Xin Zhang; Xian Jia; Song You (Biotechnology Letters, 2013)

Whole genome identification and analysis of FK506-binding protein family genes in grapevine (Vitis vinifera L.) - Lingfei Shangguan; Emrul Kayesh; Xiangpeng Leng; Xin Sun; Nicholas Kibet Korir; Qian Mu; Jinggui Fang (Molecular Biology Reports, 2013)

Role of roots in cadmium accumulation of two water spinach cultivars: reciprocal grafting and histochemical experiments - Junliang Xin; Baifei Huang; Junzhi Yang; Zhongyi Yang; Jiangang Yuan; Yangxiu Mu (Plant and Soil, 2013)

MicroRNA-153 is tumor suppressive in glioblastoma stem cells - Shiguang Zhao; Yifan Deng; Yaohua Liu; Xin Chen; Guang Yang; Yulong Mu; Daming Zhang; Jianhao Kang; Zhaoli Wu (Molecular Biology Reports, 2013)

HBV infection increases the risk of pancreatic cancer: a meta-analysis - Gang Luo; Ning-Bo Hao; Chang-Jiang Hu; Xin Yong; Mu-Han Lü; Bo-Jun Cheng; Yao Zhang; Shi-Ming Yang (Cancer Causes & Control, 2013)

Large-scale sequencing of normalized full-length cDNA library of soybean seed at different developmental stages and analysis of the gene expression profiles based on ESTs - Ai-Hua Sha; Chen Li; Xiao-Hong Yan; Zhi-Hui Shan; Xin-An Zhou; Mu-Lan Jiang; Han Mao; Bo Chen; Xia Wan; Wen-Hui Wei (Molecular Biology Reports, 2012)

The genetic profiling of preferentially expressed genes in murine splenic CD8α+ dendritic cells - Tao Li; Wu-Ying Li; Hui-Ling Bai; Hong-Bing Ma; Hu Zhang; Jiang-Mu Zhu; Xiao-Hong Li; Hong-Ying Huang; Yuan-Fang Ma; Xin-Ying Ji (Immunologic Research, 2011)

Production of a Trichoderma reesei QM9414 xylanase in Pichia pastoris and its application in biobleaching of wheat straw pulp - Jia Ouyang; Shen Wang; Yan Wang; Xin Li; Mu Chen; Qiang Yong; Shiyuan Yu (World Journal of Microbiology and Biotechnology, 2011)

Primary scientific results of Chang’E-1 lunar mission - ZiYuan Ouyang; ChunLai Li; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; JianJun Liu; Wei Zuo; Yan Su; WeiBin Wen; Wei Bian; BaoChang Zhao; et al. (Science China Earth Sciences, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Triaxial ellipsoid models of the Moon based on the laser altimetry data of Chang’E-1 - WenRui Wang; Fei Li; JianJun Liu; Xin Ren; XiaoDuan Zou; LingLi Mu; JianGuo Yan; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

New diterpenoids from the roots of Euphorbia ebracteolata Hayata - Bin Deng; Shu-Zhen Mu; Jian-Xin Zhang; Xiao-Jiang Hao (Natural Product Research, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

Differences in Action of PACAP-27 and PACAP-38 on Guinea Pig Gallbladder Smooth Muscle Using Synthetic C-terminally Modified PACAP Peptides - Mu-xin Wei; Satoru Naruse; Tsuyoshi Ozaki; Ping Hu; Victor Wray; Kiyoshi Nokihara (International Journal of Peptide Research and Therapeutics, 2009)

Completion of the sequence of rice gall dwarf virus from Guangxi, China - Heng-Mu Zhang; Xing Xin; Jian Yang; Jian-Ping Chen; Jian-Ming Wang; M. J. Adams (Archives of Virology, 2008)

Molecular characterization of the largest and smallest genome segments, S1 and S12, of Rice gall dwarf virus - Heng-Mu Zhang; Jian Yang; Xing Xin; Jian-Ping Chen; Michael J. Adams (Virus Genes, 2007)

Plants interactions between Suaeda salsa individuals are mediated by salinity stress - Hao Zhang; Jian-Na Li; Gen-Xuan Wang; Xin-Feng Dai; Mu-Qing Qiu; Ke-Feng Zheng (Acta Physiologiae Plantarum, 2007)

Molecular characterization of the largest and smallest genome segments, S1 and S12, of Rice gall dwarf virus - Heng-Mu Zhang; Jian Yang; Xing Xin; Jian-Ping Chen; Michael J. Adams (Virus Genes, 2007)